Behavioral manipulation—key to the successful global spread of the new coronavirus SARS‐CoV‐2?. Issue 3 (29th September 2020) - Bouayed, Jaouad; Bohn, Torsten
Abstract: Human‐severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) interaction can have an array of various outcomes—it could be mortal, morbid or merely carrying minor health consequences. The very rapid global spread has raised the issue whether there are further multi‐dimensional consequences of SARS‐CoV‐2 infection on human behavior, the key of its transmission. During the coronavirus crisis, odd, abnormal, and irresponsible behavior has been reported in coronavirus disease 2019 (COVID‐19) individuals, particularly in super‐spreaders, that is, persons with a high viral load, thus constituting also super‐emitters. Indeed, cases of infected persons ignoring self‐confinement orders, intentionally disregarding physical distancing and multiplying social interactions, or even deliberately sneezing, spitting or coughing were reported. While it is known that some other viruses, such as rabies and even influenza do change human behavior, this remains unclear for SARS‐CoV‐2. In this perspective, we highlight the possibility that COVID‐19 is facilitated by altered human social behavior that benefits SARS‐CoV‐2 transmission, through showcasing similar virus‐induced changed behavior by other pathogens and relating this to reports from the gray literature. Highlights: Viruses such as rabies and even influenza were reported to result in altered demeanor. SARS‐CoV‐2 behavioral manipulation may concern only a fraction of infected persons, especially super‐spreaders. SARS‐CoV‐2 may influence behavior, likely in the asymptomatic phase, favoring its prompt spread. This may explain odd behavior, e.g. disregarding confinement and deliberate viral‐spreading. This warrants further investigation, including implications for brain‐immune and brain‐gut axis.